Elderly Members’ Perspectives toward Dharma Wanita Persatuan as a Rotating Savings and Credit Association (ROSCA) - Anridho, Claudia (Universitas Tribhuwana Tunggadewi, 2025)
The Dharma Wanita Persatuan (DWP) is an organization that has a structural hierarchy from a national-governmental level institution to the smallest unit of state-relate institution. This article focused on the smallest unit of institution for state-relate-institution which is The DWP in the faculty/college level in a public university. This ethnography study wants to emphasize the meaning of DWP organization for its elderly members especially about its meaning for their personal life. The data collected by participant observation and in-depth interview then analyzed by social network theory. The results show that The DWP organization, which formed as social network, can give good motivation to keep happy and support each other life for the elderly members. The monthly lucky-draw or known as ROSCA is as a main activity which inside of it means more than money-rotation gathering but also as a place to give well-being place for its elderly members to build the inter-connected relationship. Dharma Wanita Persatuan (DWP) adalah organisasi yang memilki hierarki struktural dari lembaga tingkat pemerintah-nasional hingga unit terkecil dari institusi terafiliasi negara Indonesia. Penelitian ini fokus pada unit institusi terkecil untuk institusi dengan afiliasi negara yaitu DWP di tingkat fakultas perguruan tinggi negeri. Studi etnografi ini menekankan makna organisasi DWP bagi para anggota lanjut usia (lansia) terutama tentang makna bagi kehidupan pribadi mereka. Data dikumpulkan melalui observasi partisipasi dan wawancara mendalam, kemudian dianalisis dengan teori jaringan sosial. Hasil penelitian menunjukkan organisasi DWP, yang terbentuk sebagai jaringan sosial, dapat memberikan motivasi yang baik bagi untuk tetap bahagia dan saling mendukung bagi para anggota yang lansia. Arisan atau Asosiasi Tabungan dan Kredit Bergilir) adalah sebagai kegiatan utama yang di dalamnya memiliki makna lebih dari sekedar undian rutin bulanan bagi para anggota, namun juga menjadi tempat untuk memberikan kesejahteraan bagi para anggota lansia untuk menjalin relasi yang erat.